Glycaemic control and prevalence of hypoglycaemic events in children and adolescents with type 1 diabetes mellitus treated with insulin analogues - Plavšić, Ljiljana; Mitrović, Katarina; Todorović, Sladjana; Vuković, Rade; Milenković, Tatjana; Zdravković, Dragan (Vojnosanitetski pregled, 2014)
Background/Aim. An ideal insulin regimen for children and adolescents with type 1 diabetes mellitus (T1DM) should be physiological, flexibile and predictable, protecting against hypoglycaemia. The aim of this study was to evaluate the influence of insulin analogues on glycaemic control and the occurance of hypoglycaemic episodes in children and adolescents with T1DM. Methods. The study group consisted of 151 children and adolescents (90 boys, 61 girls) treated with human insulins for at least 12 months before introducing insulin analogues. All the patients were divided into two groups: the group I consisted of 72 (47.7%) patients treated with three injections of regular human insulin before meals and long-acting analogue (RHI/LA), and the group II of 79 (52.3%) patients treated with a combination of rapid-acting and long-acting analogue (RA/LA). The levels of glycated hemoglobin (HbA1c) and the number of hypoglycaemic episodes were assessed at the beginning of therapy with insulin analogues, and after 6 and 12 months. Results. The mean HbA1c was significantly lower in the group I (RHI/LA) after 6 months (9.15% vs 8.20%, p < 0.001) and after 12 months (9.15% vs 8.13%, p < 0.001) as well as in the group II (RA/LA) after 6 months (9.40% vs 8.24%, p < 0.001) and after 12 months of insulin analogues treatment (9.40% vs 8.38%, p < 0.001). The frequency of severe hypoglycaemia was significantly lower in both groups after 6 months (in the group I from 61.1% to 4.2% and in the group II from 54.4% to 1.3%, p < 0.001), and after 12 months (in the group I from 61.1% to 1.4% and in the group II from 54.4% to 1.3%, p < 0.001). Conclusion. Significantly better HbA1c values and lower risk of severe hypoglycaemia were established in children and adolescents with T1DM treated with insulin analogues.